2014
DOI: 10.1108/gm-12-2013-0138
|View full text |Cite
|
Sign up to set email alerts
|

Intersectionality, identity and identity work

Abstract: This document may differ from the final, published version of the research and has been made available online in accordance with publisher policies. To read and/or cite from the published version of the research, please visit the publisher's website (a subscription may be required.) 1 Intersectionality and identity: shared tenets and future research agendas for gender and identity studies Abstract Purpose: This commentary introduces the Special Issue developed from a joint research seminar of the Gender in Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 57 publications
(132 reference statements)
0
39
0
Order By: Relevance
“…As a result, their identities may become much more salient in demonstrating how these marginalized individuals are affected by the context. Major components of intersectionality encourage researchers to move beyond simplistic silos of cultural identities to explore interconnecting identity processes that can create social change (Cole, , ; Corlett & Mavin, ; May, ).…”
Section: Intersectionality As Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, their identities may become much more salient in demonstrating how these marginalized individuals are affected by the context. Major components of intersectionality encourage researchers to move beyond simplistic silos of cultural identities to explore interconnecting identity processes that can create social change (Cole, , ; Corlett & Mavin, ; May, ).…”
Section: Intersectionality As Frameworkmentioning
confidence: 99%
“…Since the expansion of intersectionality from numerous predecessors mapping its movement (Carbado et al, ), the theoretical framework has evolved to meet applicability across research, practice, policy, and pedagogy (Corlett & Mavin, ; Hancock, ). Collins and Bilge () synthesized the core tenets of intersectionality in six themes: power, complexity, social inequality, social context, social justice, and relationality.…”
Section: Intersectionality As Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous articles regarding gender inequality, as well as affirmative action policies for marginalised groups (Fernandez & Lee, 2016;Harnois, 2015;Kaiser & Spalding, 2015;Park, 2013), were reviewed for this study -yet limited research was found to determine the enabling factors utilised by racially marginalised groups to access the C-suite. Corlett and Mavin (2014), in their introduction to the Special Issue in Gender in Management on "Intersectionality, Identity and Identity work", point to the overlapping of inequalities where the intersection of two minority categories (Black and woman) constitute a distinct social position (Black woman). The whole produces unique forms of disadvantage which are more than the sum of the single categories.…”
Section: The Employment Equity Act 2003 (Ee) and Broad Based Black Ecmentioning
confidence: 99%
“…There is, however, an alternative body of research that calls for more fluid, constructivist, and critical perspective on identity in instructional communication (Mawhinney & Petchauer, 2013;Warner & Shields, 2013). It seems, however, that these topics have yet to enter classroom discussions in meaningful ways.…”
Section: Ideology In the Classroom And Intergroup Saliencementioning
confidence: 99%